The Effect of Return on Assets, Leverage, and Company Size on Tax Avoidance on Manufacturing Companies Listed on The IDX - N Heriyah (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
Tax avoidance is mostly done by taxpayers because this is legal as long as the tax avoidance is carried out not in violation of tax laws and regulations in force in Indonesia. There are several factors that affect tax avoidance including Return on assets, leverage, and company size. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange for the 2014-2017 observation period. The method of determining the sample used is the purposive sampling method with a sample of 159. Based on the results of multiple linear regression analysis, the results obtained that the variable Return On Assets, leverage, and Company Size positive effect on tax avoidance by manufacturing companies listed on the Indonesia Stock Exchange for the 2012-2017 observation year period.